1989
DOI: 10.1159/000293646
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Cyst, Dermoid Cyst and Mucinous Cystadenoma Sonographically Evidenced in the Same Ovary

Abstract: We treated a patient with an ovarian tumor histologically consisting of an endometrial cyst, dermoid cyst and mucinous cystadenoma, in the same ovary. A comparative study between ultrasonic and histological findings was done. The usefulness, drawbacks and limitations in the ultrasonic evaluation of ovarian tumors are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Our literature search retrieved several reports of mucinous cystadenoma occurring synchronously with other ovarian tumors such as endometrial cyst and dermoid cyst [4], anaplastic carcinoma [18], clear-cell carcinoma [19], choriocarcinoma [20], granulosa cell tumor, and mature teratoma [21]. Morris et al [22] suggested that some mucinous tumors may derive from germ cells, for instance, in mature teratoma; and our report supports this hypothesis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our literature search retrieved several reports of mucinous cystadenoma occurring synchronously with other ovarian tumors such as endometrial cyst and dermoid cyst [4], anaplastic carcinoma [18], clear-cell carcinoma [19], choriocarcinoma [20], granulosa cell tumor, and mature teratoma [21]. Morris et al [22] suggested that some mucinous tumors may derive from germ cells, for instance, in mature teratoma; and our report supports this hypothesis.…”
Section: Discussionsupporting
confidence: 82%
“…Mature or immature recurrence may occur during follow-up [1][2][3]. Synchronous ovarian teratoma with mucinous cystadenoma has been reported in a few patients [4][5][6][7][8][9]. Mucinous cystadenoma is extremely rare during childhood [10].…”
mentioning
confidence: 99%
“…Mucinous neoplasms occur rarely in association with cystic teratoma, Sertoli‐Leydig cell tumor, granulosa cell tumor and carcinoid tumor 20 . Only a few cases of dermoid cyst and benign cystadenoma in the same ovary have been reported 21,22 . We did not come across any cases of dermoid cyst and yolk sac tumor in the same ovary in the literature.…”
Section: Discussionmentioning
confidence: 94%